The Trump Administration’s Policy to Contain China in The Field of Technology - Sh. Zhang (Проблемы постсоветского пространства)
The article examines the Trump administration's policy to contain China in the field of technology. Particular attention is paid to the content of this policy, its reasons and impact on Sino-US relations. Since taking office, Trump has begun to regard China as a competitor of USA in the global science and technology field. The Trump administration has tried to prevent free technological exchanges with China. The United States’ containment policy has weakened the strategic mutual trust between China and the United States and has aggravated the tension in Sino-US relations. Despite the efforts of the United States, it failed to influence China's technological development. The conclusion of the article is that China continues to pursue an active technology policy to mitigate the negative impact of the US containment policy.